Biomedical Engineering, Trends in Electronics Communications and Software - Laskovski, Anthony N. (IntechOpen, 2011)
Rapid technological developments in the last century have brought the field of biomedical engineering into a totally new realm. Breakthroughs in material science, imaging, electronics and more recently the information age have improved our understanding of the human body. As a result, the field of biomedical engineering is thriving with new innovations that aim to improve the quality and cost of medical care. This book is the first in a series of three that will present recent trends in biomedical engineering, with a particular focus on electronic and communication applications. More specifically: wireless monitoring, sensors, medical imaging and the management of medical information.